Inhibition activity of tomato endophyte Bacillus velezensis FQ-G3 against postharvest Botrytis cinerea - Feng, Baozhen; Li, Peiqian; Chen, Dandan; Ding, Chunshuang (Folia microbiologica, 2024)
Grey mold, caused by Botrytis cinerea, is a widespread and harmful disease of tomato. Biocontrol agents derived from endophytic bacteria are known to hold great potential for inhibition of phytopathogen. We conducted this study to explore the tomato endophytic strains with inhibition activity against B. cinerea. Endophytic strain Bacillus velezensis FQ-G3 exhibited excellent inhibition activity against B. cinerea. Inhibitory effects against B. cinerea were investigated both in vitro and in vivo. The in vitro assays displayed that FQ-G3 could significantly inhibit mycelia growth with inhibition rate of 85.93%, and delay conidia germination of B. cinerea. Tomato fruit inoculated with B. velezensis FQ-G3 revealed lower grey mold during treatment. The antifungal activity was attributed to activation of defense-related enzymes, as evidenced by the higher levels of peroxidase, polyphenol oxidase, and phenylalanine ammonia lyase in tomatoes after inoculation. In addition, scanning electron microscope was applied to elucidate the interaction between endophytes and pathogen, and bacterial colonization and antibiosis appeared to be the underlying mechanisms that FQ-G3 could suppress growth of B. cinerea. Collectively, our present results suggested that FQ-G3 may potentially be useful as a biocontrol agent in postharvest tomatoes.
Keywords: Endophytes; Bacillus; endofyty; nemoci rostlin; Botrytis; Plant Diseases; Solanum lycopersicum